التصميم التعليمي كاستراتيجية لضمان جودة أستاذ التربية البدنية والرياضية في مرحلة التعليم الابتدائي دراسة ميدانية بابتدائيات بلدتي ونوغة وبني يلمان بالمسيلة - حواسي ، السعيد; Supervisor : بوخرص ، رمضان (Mohamed Boudiaf University of M'Sila, 2025)
الملخص: عنوان الدراسة: التصميم التعليمي كاستراتيجية لضمان جودة أستاذ التربية البدنية والرياضية في مرحلة التعليم الابتدائي-دراسة ميدانية بابتدائيات بلدتي ونوغة وبني يلمان بالمسيلة أهداف الدراسة: -معرفة مدى اعتبار التصميم التعليمي كاستراتيجية في ضمان جودة أداء أستاذ التربية البدنية والرياضية في مرحلة التعليم الابتدائي. - معرفة مدى إسهام تحديد الأهداف التعليمية في التخطيط الجيد والفعال لدرس التربية البدنية والرياضية - معرفة مدى إسهام تحليل خصائص المتعلمين في تفهم أهداف التربية البدنية والرياضية - معرفة مدى إسهام تحليل محتوى تعليمي في عملية تنفيذ الدرس في التربية البدنية والرياضية - معرفة مدى إسهام صياغة الأهداف الأدائية في إنجاز المهام التعليمية بإتقان وإمكانية تقويمها. التساؤل العام الدراسة: هل يعتبر التصميم التعليمي كاستراتيجية في ضمان جودة أداء أستاذ التربية البدنية والرياضية في مرحلة التعليم الابتدائي؟ التساؤلات الجزئية: 1-هل لتحديد الأهداف التعليمية يسهم في التخطيط الجيد والفعال لدرس التربية البدنية والرياضية؟ 2-هل لتحليل خصائص المتعلمين يسهم في تفهم أهداف التربية البدنية والرياضية؟ 3-هل لتحليل محتوى تعليمي يسهم في عملية تنفيذ الدرس في التربية البدنية والرياضية؟ 4-هل لصياغة الأهداف الأدائية تسهم في إنجاز المهام التعليمية بإتقان وإمكانية تقويمها؟ الفرضية العامة للدراسة: يعتبر التصميم التعليمي كاستراتيجية في ضمان جودة أداء أستاذ التربية البدنية والرياضية في مرحلة التعليم الابتدائي. الفرضيات الجزئية 1-تحديد الأهداف التعليمية يسهم في التخطيط الجيد والفعال لدرس التربية البدنية والرياضية 2-تحليل خصائص المتعلمين يسهم في تفهم أهداف التربية البدنية والرياضية 3-تحليل محتوى تعليمي يسهم في عملية تنفيذ الدرس في التربية البدنية والرياضية 4-صياغة الأهداف الأدائية تسهم في إنجاز المهام التعليمية بإتقان وإمكانية تقويمها. المنهج المتبع في الدراسة: تم استخدام المنهج الوصفي الأدوات المستخدمة في الدراسة: تم استخدام استمارة الاستبيان كأداة لجمع البيانات الكلمات المفتاحية التصميم التعليمي، الاستراتيجية، جودة الأداء، أستاذ التربية البدنية والرياضية، التعليم الابتدائي بالإنجليزية: Instructional design, strategy, quality of performance, professor of physical and sports education, primary education جاء هذا البحث في 06 فصول: الفصل الأول: الإطار المنهجي للدراسة، وقد تناولنا فيه طرح إشكالية الدراسة وتساؤلاتها، بالإضافة إلى فرضيات الدراسة، أسباب اختيار الموضوع، أهمية وأهداف الدراسة، ثم عرضنا بعض الدراسات السابقة والمشابهة والتعليق عليها. الفصل الثاني: تناولنا فيه الإطار المفاهيمي والمعرفي للتصميم التعليمي الفصل الثالث: تطرقنا فيه الإطار المفاهيمي والمعرفي لجودة الأداء التعليمي والتربوي الفصل الرابع: الإطار المنهجي للدراسة، وتناولنا فيه الدراسة الاستطلاعية، مجالات الدراسة، المنهج المتبع في الدراسة، مجتمع وعينة الدراسة، أدوات الدراسة وأخيرا الأدوات الإحصائية المستخدمة في الدراسة. الفصل الخامس: عرض نتائج الدراسة وتفسيرها. الفصل السادس: الاستنتاجات والاقتراحات. من أهم النتائج التي توصل إليها الباحث: - تحديد الأهداف التعليمية يسهم في التخطيط الجيد والفعال لدرس التربية البدنية - تحليل خصائص المتعلمين يسهم في فهم أهداف التربية البدنية والرياضية - تحليل المحتوى التعليمي يسهم في عملية تنفيذ الدرس في التربية البدنية والرياضية - تحليل المحتوى التعليمي يسهم في عملية تنفيذ الدرس في التربية البدنية والرياضية - يساهم التصميم التعليمي كاستراتيجية في ضمان جودة أداء أستاذ التربية البدنية والرياضية في مرحلة التعليم الابتدائي. أهم التوصيات: - دمج التصميم التعليمي في التكوين المستمر بحيث يتم إدماج مفاهيم ونماذج التصميم التعليمي ضمن برامج تكوين أساتذة التربية البدنية، مع التركيز على التخطيط التربوي، تحديد الأهداف السلوكية، اختيار الوسائل التعليمية، وتصميم أنشطة ملائمة للفئة العمرية. - إعداد دليل عملي بيداغوجي خاص بأساتذة التربية البدنية يحتوي على خطوات تطبيق التصميم التعليمي في إعداد وتنفيذ الدروس، مع أمثلة تطبيقية تتناسب مع خصوصية الحصص البدنية. - تطوير برامج تدريبية ميدانية وتنظيم دورات وورشات تطبيقية داخل المؤسسات التربوية لتدريب الأساتذة على نماذج التصميم التعليمي وربطها بالتقويم التكويني والتقويم النهائي للحصص.   Summary: Study title: Educational design as a strategy to ensure the quality of physical and sports education teachers in the primary education stage - a field study in the primary schools of the towns of Nougat and Beni Yelman in M’sila Study objectives: -Knowing the extent to which instructional design is considered as a strategy in ensuring the quality of performance of the physical education and sports teacher in primary education. -To know the extent to which the definition of educational objectives contributes to a good and effective planning of a physical education and sports lesson -Knowing the extent to which the analysis of learners' characteristics contributes to understanding the objectives of physical education and sports -Knowing the extent to which analyzing educational content contributes to the lesson implementation process in physical education and sports -Knowing the extent to which formulating performance objectives contributes to the completion of educational tasks with mastery and the possibility of evaluating them. General Question Study: Is instructional design considered as a strategy in ensuring the quality of performance of the physical education and sports teacher in the primary education stage? Partial questions: 1-Does setting educational goals contribute to good and effective planning for a physical education and sports lesson? 2-Does analyzing learners’ characteristics contribute to understanding the goals of physical education and sports? 3-Does analyzing educational content contribute to the process of implementing the lesson in physical education and sports? 4-Does formulating performance goals contribute to completing educational tasks with mastery and the possibility of evaluating them? General hypothesis of the study: Instructional design is considered as a strategy in ensuring the quality of performance of the physical and sports education teacher in primary education. Partial hypotheses 1- Setting educational goals contributes to good and effective planning for a physical education and sports lesson 2- Analyzing the characteristics of learners contributes to understanding the goals of physical education and sports 3- Analyzing educational content that contributes to the process of implementing the lesson in physical education and sports 4-Formulating performance goals contributes to completing educational tasks with mastery and the possibility of evaluating them. Method followed in the study: Descriptive method was used Instruments used in the study: The questionnaire form was used as a data collection instrument Keywords : Instructional design, strategy, quality of performance, professor of physical and sports education, primary education This research came in 6 chapters: Chapter One: The methodological framework of the study, in which we discussed the study’s problem and questions, in addition to the study’s hypotheses, the reasons for choosing the topic, the importance and objectives of the study, and then we presented some previous and similar studies and commented on them. Chapter 2, in which we consider the conceptual and epistemological framework of instructional design Chapter Three: We discussed the conceptual and cognitive framework for the quality of educational and pedagogical performance Chapter Four: The methodological framework of the study, in which we discussed the exploratory study, the areas of study, the method followed in the study, the population and sample of the study, the study tools, and finally the statistical tools used in the study. Chapter 5: Presentation and interpretation of study results. Chapter 6: Conclusions and suggestions. Among the most important findings reached by the researcher: -Setting educational goals contributes to good and effective planning of the physical education lesson -Analyzing the characteristics of learners contributes to understanding the goals of physical education and sports -The analysis of the educational content contributes to the process of implementing the lesson in physical and sports education -The analysis of the educational content contributes to the process of implementing the lesson in physical and sports education -Didactic design contributes as a strategy to ensure the quality of the performance of the Physical Education and Sports teacher in the Primary Education stage. The most important recommendations: -Integrating educational design into continuing training so that educational design concepts and models are integrated into physical education teachers’ training programs, with a focus on educational planning, setting behavioral goals, choosing educational methods, and designing activities appropriate for the age group. -Preparation of a practical pedagogical manual for physical education teachers containing steps for applying instructional design in the preparation and implementation of lessons, with practical examples appropriate to the specificity of physical classes. -Developing field training programs and organizing applied courses and workshops within educational institutions to train teachers on educational design models and linking them to the formative evaluation and the final evaluation of classes.
Keywords: التصميم التعليمي; الاستراتيجية; جودة الأداء; أستاذ التربية البدنية والرياضية